City Branding: Leveraging Historical Heritage with Kyrenia Castle - Pooyanmehr , Mahrokh; Gurdalli , Huriye (Journal of Ecohumanism, 2025)
In this research, as cities fight to draw businesses, investors, and visitors, city branding has grown in significance in the global environment. The ancient site of Kyrenia Castle is a major historical treasure for Kyrenia, a charming seaside city in Cyprus. With origins in the Byzantine era, this ancient iconic structure has been influenced by several different civilizations, notably the Lusignans, Venetians, and Ottomans. Kyrenia Castle’s architectural prominent status and rich history make it an underutilized asset in the city’s current branding initiatives. The purpose of this study is to investigate how Kyrenia Castle may be used to improve the city brand of Kyrenia, which will increase tourism, promote pride among citizens, and stimulate economic growth. The goal of this study is to offer strategic insights and useful recommendations for stakeholders and municipal authorities through assessing the castle’s historical relevance and potential as a key component of city branding.